Model Integrasi Teknologi Informasi dan Komunikasi dalam Pembelajaran Jarak Jauh - Muhammad Yaumi; Muljono Damopolii (Al-Musannif, 2019)
The purposes of the study were to analyze the availability of supporting infrastructure and facilities in integrating ICT, describe the utilization model of information and communication technology used in the distance learning process, and reveal the interaction model implemented in distance learning classes by using ICT. This study used qualitative research by involving distant classes in cooperation between post graduate program of UINAM, STAIN Palopo, and UMPAR. The methods in collecting data consisted of observation, interviews and documentation. The data analysis included data reduction, data display, and drawing conclusion and verification. The results showed that the integration model of information and communication technologies used in distance learning under the cooperation class between post graduate program at the UINAM, STAIN Palopo, and UMPAR covered (1) the identification of appropriate sources that are in the category of fairly complete, (2) the use of ICT in distance learning can be categorized into two parts; providing materials and learning activities, and (3) the forms of interaction are faculty-student interaction, student-student interaction, and faculty-student and learning resources interaction.